Dimensional analysis - Gibbings, J.C.; SpringerLink (Online service). (London Springer London Imprint: Springer, 2011)
For experiments, dimensional analysis enables the design, checks the validity, orders the procedure and synthesis the data. Additionally it can provide relationships between variables where standard analysis is not available. This widely valuable analysis for engineers and scientists is here presented to the student, the teacher and the researcher. It is the first complete modern text that covers developments over the last three decades while closing all outstanding logical gaps. Dimensional Analysis also lists the logical stages of the analysis, so showing clearly the care to be taken in its use while revealing the very few limitations of application. As the conclusion of that logic, it gives the author's original proof of the fundamental and only theorem. Unlike past texts, Dimensional Analysis includes examples for which the answer does not already exist from standard analysis. It also corrects the many errors present in the existing literature by including accurate solutions. Dimensional Analysis is written for all branches of engineering and science as a teaching book covering both undergraduate and postgraduate courses, as a guide for the lecturer and as a reference volume for the researcher.
1. An Elementary Introduction -- 2. Concepts, Dimenstions and Units -- 3. The Pi-theorem -- 4. Development of Dimensional Analysis -- 5. The Choice of Dimensions -- 6. Supplementation of Derivations -- 7. Systematic Experiment -- 8. Analytical Results -- 9. Model Testing -- 10. Assessing Experimental Correlations -- 11. Similar Systems.
Electronic reproduction.
Keywords: Dimensional analysis